The protectionist's progress: Year 1 - Uri Dadush (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
President Trump's actions on trade have not quite matched his rhetoric, but the worst may be to come. Though the political opposition to his protectionism is formidable, so are his conviction and determination and he possesses a wide array of instruments to pursue his goals. The trade doctrine he has espoused makes for trade policy instability both at home and abroad. It may lead to a large deterioration in the operating environment of international business. America's trade-dependent industries and her trading partners should not wait. They need to anticipate and deter the administration's actions. Policies must be adjusted to minimize the damage to world trade.
Keywords: F14; 330; trade; protectionism; mercantilism; trade remedies; geopolitics